2021
DOI: 10.1115/1.4050374
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on Impacts of COVID19 on Sustainable Buildings and Cities

Abstract: The pandemics of COVID19 has disrupted all aspects of our lives in many ways since it was first detected in the early part of the year 2020; personal and professional lives were impacts, work places, learning environments, businesses, commerce, and industry. This complex situation that places buildings at the center of the human activity raises many questions about our state of knowledge and technology to face these extraordinary challenges presented by a global pandemics. To reflect on these complex questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The Covid-19 pandemic and quarantine have caused architects to reconsider the planning and constructing of residential buildings in terms of area and design of spaces inside the future home. Also, to become sustainable residential buildings that depend on natural ventilation, good natural lighting, and open green spaces [17] , [26] . some studies have shown how mental and physical health is related to green open spaces and how important they are.…”
Section: Introductionmentioning
confidence: 99%
“…The Covid-19 pandemic and quarantine have caused architects to reconsider the planning and constructing of residential buildings in terms of area and design of spaces inside the future home. Also, to become sustainable residential buildings that depend on natural ventilation, good natural lighting, and open green spaces [17] , [26] . some studies have shown how mental and physical health is related to green open spaces and how important they are.…”
Section: Introductionmentioning
confidence: 99%